PERBEDAAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII MTs PEKAN TEBIH YANG MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) - -, Yuswaiti; -, Arcat; Deswita, Hera (Universitas Pasir Pengaraian, 2015)
This research aims to determine wheter there are difference in cooperetif learning model NHT and TPS on learning outcomes mathematics. This type of research is a quasi-experimental research, which its population is class VIII MTs Pekan Tebih. The sampling technique used is saturated sample technique, which means the population as well as the sample. Grade sample consisted of experimental class first and second exsperiment, where the first experimental class applied learning model NHT while the second exsperiment class applied learning model TPS. The result of the calculation, t =2.93 and table =2.026 wich means hitungt t>ttable at 5% significance level. The hypothesis is accepted. Thus there are difference in mathematics learning outcomes of students who are taught using cooperative learning model NHT and TPS.